Quantum toy model for black-hole backreaction - Maia, Clovis; Schuetzhold, Ralf (Amer Physical Soc, 2007)
We propose a simple quantum field theoretical toy model for black-hole evaporation and study the backreaction of Hawking radiation onto the classical background. It turns out that the horizon is also pushed back in this situation (i.e., the interior region shrinks) though this backreaction is not caused by energy conservation but by momentum balance. The effective heat capacity and induced entropy variation can have both signs-depending on the parameters of the model.